Study Of Critical Disadvantages System Catur Varna To Concept Catur Kasta In Civil Society Bali Hindu - I Made Purana (Jayapangus Press, 2022)
The people apanage of Bali know the concept of Kasta. Such stratification creates different views between the Tri Wangsa and jaba groups. The Tri Wangsa want an acribed status, whereas the Sudra or Jaba group want the achieved status, which in turn leads to polemics among the people of Bali apanage. As a qualitative study with a cultural perspective, this study aims to reveal and analyze more clearly the blurring of the varna system into a kasta concept in Balinese Hindu society. Data sources are extracted based on bibliographic or documentary data. Data collection using reading techniques and recording techniques. Data analysis on the problem is done by qualitative descriptive analysis and comparative analysis. The results showed that the blurring of the varna system into a kasta concept is inseparable from the royal politics of its time. The traditional educational system originating from Hindu literature and religion can only be enjoyed by the upper layers, the brahmins and the knights, while the sudra or jaba classes are strictly prohibited. The Kasta architects of Bali in the past few centuries, so expertly exploit the situation of the backwardness of Hindus outside the brahmans and the knights, so the teachings of Hinduism are manipulated in terms of caste naming. The elements of caste plagiarize the elements of varna that are indeed Hindu teachings. In addition, Dutch colonial politics is also very influential on the order of life in Bali, which causes problems in the system of social status. The Dutch government has not fully implemented the modern system of government. This is evident in the system of appointment of new employees (civil servants). The Dutch government has not carried out according to rational legal criteria, but still uses the traditional system of judging a person in terms of the height of the Kasta, not in terms of ability. Therefore, it is necessary to increase knowledge of village manners in the field of customary law and knowledge of village manners in the field of religion according to what is stated in the Hindu scriptures.